Analisis Pengaruh Suku Bunga, Tingkat Pengangguran, dan Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi Pulau Jawa - Assyifa Eka Nabila; Ia Haerunisa; Sofiyatun Najwa (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2026)
This study analyses the effect of interest rates, unemployment rates, and the Human Development Index (HDI) on economic growth in three major provinces of Indonesia, namely DKI Jakarta, West Java, and East Java during the period 2016–2023 using a panel data approach. The secondary data used came from the Central Statistics Agency and Bank Indonesia. The analysis method used panel data regression with Chow, Hausman, and Lagrange Multiplier tests to select the best model and classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results show that the Common Effect Model is most appropriate for describing the relationship between variables in this study. Interest rates do not have a significant effect on economic growth, while unemployment rates have a significant negative effect and HDI has a significant positive effect on economic growth. The regression model with robust standard error is able to explain 94.10% of the variation in Gross Regional Domestic Product (GRDP) in the three provinces. These findings provide empirical evidence that improving the quality of human resources and reducing unemployment rates are key to driving economic growth in Indonesia's major regions.